Pengaruh literasi keuangan, locus of control, dan etnis terhadap pengambilan keputusan investasi - Sofi Ariani; Putri Asiza Agustien Aulia Rahmah; Yurisha Ramadhani Putri; Maulidatur Rohmah; Antika Budiningrum; Lutfi Lutfi (STIE Perbanas Surabaya, 2015)
The purpose of this research is to examine the influence of financial literacy, locus of control, and ethnic on investment decision. This research uses multiple regression analy-sis technique and a sample of 199 investors who put their funds in bank account and real asset in Surabaya and Madura region. The results shows that financial literacy, internal locus of control, external locus of control, and ethnic do not have significant impact si-multaneously on investment decision, while locus control is only variable that has signif-icant partial impact investment decision. This finding implies that goof financial literacy per se will not result in a good investment decision without accompanied by good inter-nal control. Therefore, policy makers should not only focus on financial literacy educa-tion but also increase public awareness about the importance of self-control when making investment decisions.